Solubility of CO2 in an aqueous ammonium based ionic liquid - Safdar, R. (Trans Tech Publications Ltd, 2014)
The aim of this research is to find out the potential usage of water miscible ammonium based ionic liquids (ILs) towards CO2 capture. To measure the solubility of CO2 in 55 wt. aqueous solution of Tetra butyl ammonium hydroxide (TBAOH), the experiments were carried out using high pressure solubility cell. Solubilities were determined in the temperature range of (303.15 to 333.15) K by varying the pressure from (2 to 10) bar and are reported as loading capacity (mol CO2/mol TBAOH). The solubility of CO2 in this aqueous IL decreased with increasing temperature and increased with increasing pressure. Â© 2014 Trans Tech Publications, Switzerland.